Spatial analysis For educational services in the city of Sulaymaniyah: Using the multiple regression model - Al-Hiti, Dr. Mazin Abdulrahman; Hindi Aliwi, Yunus (Al-Adab Journal, 2021)
The educational services is consider very important , it should be available as a society services whether it is a given services or an area occupied including Within urban space , The researcher depend on the statistics as a modern way in geographical studies to examine the efficiency and sufficiency to the services in Sulaymaniyah city which is acted in shape of getting down which is multiple that is discovered according to the toning groups and changing's groups making weakness in services distributed according to the population area and the size of population that is indicates no efficiency comparing to the population to the number of students and the number of schools comparing to the number of buildings in the area.